2011
DOI: 10.1143/apex.5.012601
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Synthesis of Rare-Earth and Phosphorus Codoped Monolithic Silica Glasses from a Cosolvent-Free Phase-Separating System

Abstract: A cosolvent-free sol-gel method to prepare monolithic transparent silica glasses doped by rare-earth ions at high concentrations has been developed. Despite the simple solution composition, the reaction mixture undergoes a macroscopic phase separation in parallel with the gelation, and the resultant macropores make it possible to considerably shorten the processing time by facilitating the drying and sintering of gels. The addition of a small amount of phosphorus significantly enhances the dissolution of rare-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The concentration of Nd 3+ ions corrected for the loss was ³2.0 © 10 20 cm ¹3 for the Al-free glass and ³1.8 © 10 20 cm ¹3 for the Al-codoped glass. It was also found that the loss of Nd 3+ ions from the NdP codoped glass, which we reported previously, 31) was ³9 « 3% and was comparable to that of the Al-free glass. Figure 3 shows XRD patterns of the crushed Al-free and Al-codoped glasses.…”
Section: ¹1supporting
confidence: 84%
“…The concentration of Nd 3+ ions corrected for the loss was ³2.0 © 10 20 cm ¹3 for the Al-free glass and ³1.8 © 10 20 cm ¹3 for the Al-codoped glass. It was also found that the loss of Nd 3+ ions from the NdP codoped glass, which we reported previously, 31) was ³9 « 3% and was comparable to that of the Al-free glass. Figure 3 shows XRD patterns of the crushed Al-free and Al-codoped glasses.…”
Section: ¹1supporting
confidence: 84%
“…Despite the high SiOH concentration (∼10 20 cm −3 ), the Tb P codoped glasses exhibit bright green PL under ultraviolet (UV) photoexcitation, as shown in Fig. 11 [136]. The PL decay kinetics is a single exponential, and the PL intensity increases proportionally with Tb to Si molar ratios up to 0.02 (∼5 × 10 4 ppmw or ∼5 wt.% Tb 2 O 3 ), while maintaining the PL decay constant at ∼4.0 ms.…”
Section: Rare-earth Dopingmentioning
confidence: 99%
“…Reprinted with permission from Ref. [136]; Copyright 2012 The Japan Society of Applied Physics Fig. 12.…”
Section: Incorporation Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus is employed as a dopant to enhance the dissolution of rare-earth ions in silica glasses. 17 II. Experimental…”
Section: Introductionmentioning
confidence: 99%